Peran Politik Kyai dalam Pengendalian Konflik Pemilihan Kepala Desa (Pilkades) - Rozi, Syaikhu; Saifudin, Saifudin; Rohmad, M. Ali; Syarif, M. (Proceedings of Annual Conference for Muslim Scholars, 2019)
As a reality, conflict can occur anywhere, whenever and experienced by anyone due to certain factors, one of which is the process and the results of the Election of Village Heads (PILKADES). Election of Village Head which is carried out directly to elect village leaders, in practice it is often to use money politics and "black campaigns". The PILKADES conflict is rooted in the interests of Botoh (gambling bettors), entrepreneurs and some of their supporters who are trying to win one of the KADES candidates. Efforts are being taken, among others, by developing issues based on personality character and social values ​​to attack the opposing parties resulting in a war of issues and psychological conflicts that manifest in the form of mobilization of time. However, the mobilizations of the people do not develop into physical violence because the conflict can be effectively controlled by the kyai. Implementation of the role of Kyai in controlling PILKADES conflicts are carried out these ways: 1) engaging in informal political discussion; 2) individual communication with political officials; 3) carry out education to the community to strengthen social ties between them, and 4) plunge directly into the field to control and disband the people